Assisted Reproductive Technology Surveillance — United States, 2016 - Sunderam, Saswati (MMWR Surveill Summ, 2019)
PROBLEM/CONDITION: Since the first U.S. infant conceived with assisted reproductive technology (ART) was born in 1981, both the use of ART and the number of fertility clinics providing ART services have increased steadily in the United States. ART includes fertility treatments in which eggs or embryos are handled in the laboratory (i.e., in vitro fertilization [IVF] and related procedures). Although the majority of infants conceived through ART are singletons, women who undergo ART procedures are more likely than women who conceive naturally to deliver multiple-birth infants. Multiple births pose substantial risks for both mothers and infants, including obstetric complications, preterm delivery (<37 weeks), and low birthweight (<2,500 g). This report provides state-specific information for the United States (including the District of Columbia and Puerto Rico) on ART procedures performed in 2016 and compares birth outcomes that occurred in 2016 (resulting from ART procedures performed in 2015 and 2016) with outcomes for all infants born in the United States in 2016. PERIOD COVERED: 2016. DESCRIPTION OF SYSTEM: In 1995, CDC began collecting data on ART procedures performed in fertility clinics in the United States as mandated by the Fertility Clinic Success Rate and Certification Act of 1992 (FCSRCA) (Public Law 102–493 [October 24, 1992]). Data are collected through the National ART Surveillance System (NASS), a web-based data collection system developed by CDC. This report includes data from 52 reporting areas (the 50 states, the District of Columbia, and Puerto Rico). RESULTS: In 2016, a total of 197,706 ART procedures (range: 162 in Wyoming to 24,030 in California) with the intent to transfer at least one embryo were performed in 463 U.S. fertility clinics and reported to CDC. These procedures resulted in 65,964 live-birth deliveries (range: 57 in Puerto Rico to 8,638 in California) and 76,892 infants born (range: 74 in Alaska to 9,885 in California). Nationally, the number of ART procedures performed per 1 million women of reproductive age (15–44 years), a proxy measure of the ART use rate, was 3,075. ART use rates exceeded the national rate in 14 reporting areas (Connecticut, Delaware, the District of Columbia, Hawaii, Illinois, Maryland, Massachusetts, New Hampshire, New Jersey, New York, Pennsylvania, Rhode Island, Utah, and Virginia). ART use exceeded 1.5 times the national rate in nine states, including three (Illinois, Massachusetts, and New Jersey) that also had comprehensive mandated health insurance coverage for ART procedures (i.e., coverage for at least four oocyte retrievals). Nationally, among ART transfer procedures for patients using fresh embryos from their own eggs, the average number of embryos transferred increased with increasing age (1.5 among women aged <35 years, 1.7 among women aged 35–37 years, and 2.2 among women aged >37 years). Among women aged <35 years, the national elective single-embryo transfer (eSET) rate was 42.7% (range: 8.3% in North Dakota to 83.9% in Delaware). In 2016, ART contributed to 1.8% of all infants born in the United States (range: 0.3% in Puerto Rico to 4.7% in Massachusetts). ART also contributed to 16.4% of all multiple-birth infants, including 16.2% of all twin infants and 19.4% of all triplets and higher-order infants. ART-conceived twins accounted for approximately 96.5% (21,455 of 22,233) of all ART-conceived infants born in multiple deliveries. The percentage of multiple-birth infants was higher among infants conceived with ART (31.5%) than among all infants born in the total birth population (3.4%). Approximately 30.4% of ART-conceived infants were twins and 1.1% were triplets and higher-order infants. Nationally, infants conceived with ART contributed to 5.0% of all low birthweight (<2,500 g) infants. Among ART-conceived infants, 23.6% had low birthweight compared with 8.2% among all infants. ART-conceived infants contributed to 5.3% of all preterm (gestational age <37 weeks) infants. The percentage of preterm births was higher among infants conceived with ART (29.9%) than among all infants born in the total birth population (9.9%). The percentage of ART-conceived infants who had low birthweight was 8.7% among singletons, 54.9% among twins, and 94.9% among triplets and higher-order multiples; the corresponding percentages among all infants born were 6.2% among singletons, 55.4% among twins, and 94.6% among triplets and higher-order multiples. The percentage of ART-conceived infants who were born preterm was 13.7% among singletons, 64.2% among twins, and 97.0% among triplets and higher-order infants; the corresponding percentages among all infants were 7.8% for singletons, 59.9% for twins, and 97.7% for triplets and higher-order infants. INTERPRETATION: Multiple births from ART contributed to a substantial proportion of all twins, triplets, and higher-order infants born in the United States. For women aged <35 years, who typically are considered good candidates for eSET, on average, 1.5 embryos were transferred per ART procedure, resulting in higher multiple birth rates than could be achieved with single-embryo transfers. Of the four states (Illinois, Massachusetts, New Jersey, and Rhode Island) with comprehensive mandated health insurance coverage, three (Illinois, Massachusetts, and New Jersey) had rates of ART use >1.5 times the national average. Although other factors might influence ART use, insurance coverage for infertility treatments accounts for some of the difference in per capita ART use observed among states because most states do not mandate any coverage for ART treatment. PUBLIC HEALTH ACTION: Twins account for almost all of ART-conceived multiple births born in multiple deliveries. Reducing the number of embryos transferred and increasing use of eSET, when clinically appropriate, could help reduce multiple births and related adverse health consequences for both mothers and infants. Because multiple-birth infants are at increased risk for numerous adverse sequelae that cannot be ascertained from the data collected through NASS alone, long-term follow-up of ART infants through integration of existing maternal and infant health surveillance systems and registries with data available from NASS might be useful for monitoring adverse outcomes.